Improved Performance of Wolo Irrigation Area through Integrated Management and e-PAKSI/eA-AMPIS Application - Hasrat, Andi; Sukri, Ahmad Syarif; Ilham, Ilham; Wibowo, Dwiprayogo (Brawijaya University, 2025)
The performance assessment of the Wolo Irrigation Area (WIA) is crucial for ensuring efficient water management and sustainable agricultural productivity. This study evaluates WIA’s operational performance using the e-PAKSI or eA-AMPIS application as a digital platform designed for integrated irrigation performance monitoring. The assessment results show a performance index of 60.44%, indicating that several functional aspects require improvement. Unlike previous studies that relied solely on manual field evaluation, this research integrates digital data collection through electronic Performance Assessment and Irrigation System Information (e-PAKSI) to provide more accurate, real-time, and traceable performance indicators. The findings highlight the need for targeted management strategies focusing on infrastructure maintenance, operational efficiency, and community-based institutional strengthening. Implementing these strategies can enhance WIA’s functionality and support sustainable irrigation management in similar regional systems.